2020
DOI: 10.48550/arxiv.2006.05518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MVLidarNet: Real-Time Multi-Class Scene Understanding for Autonomous Driving Using Multiple Views

Abstract: Autonomous driving requires the inference of actionable information such as detecting and classifying objects, and determining the drivable space. To this end, we present a two-stage deep neural network (MVLidarNet) for multi-class object detection and drivable segmentation using multiple views of a single LiDAR point cloud. The first stage processes the point cloud projected onto a perspective view in order to semantically segment the scene. The second stage then processes the point cloud (along with semantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Among these three focused methods, [27] scores best in terms of mIoU and mAP values, with superior FPS, which are 31.30, 65.50, and 65.5, respectively. The reported results over the SemanticKITTI dataset indicate a better performance of the method in [51], achieving well-balanced mIoU and FPS scores, i.e., 52.20 and 92, respectively. Finally, the method in [65] performs comparatively better than the one in [107], by offering best values of the mIoU, mAP, and FPS scores (75.70, 83.60, and 19.5, respectively).…”
Section: Quantitative Analysis Of Scene Segmentation Methods For Admentioning
confidence: 84%
“…Among these three focused methods, [27] scores best in terms of mIoU and mAP values, with superior FPS, which are 31.30, 65.50, and 65.5, respectively. The reported results over the SemanticKITTI dataset indicate a better performance of the method in [51], achieving well-balanced mIoU and FPS scores, i.e., 52.20 and 92, respectively. Finally, the method in [65] performs comparatively better than the one in [107], by offering best values of the mIoU, mAP, and FPS scores (75.70, 83.60, and 19.5, respectively).…”
Section: Quantitative Analysis Of Scene Segmentation Methods For Admentioning
confidence: 84%
“…Multi-view fusion-based methods combine voxel-based, projection-based and/or point-wise operations for LiDAR point clouds segmentation. To extract more semantic information, some recent methods [35], [36], [37], [38], [39], [40], [41], [7], [8] blend two or more different views together. For instance, [38], [39] combine point-wise information from BEV and range-image in early-stage, and then feed it to the subsequent network.…”
Section: B Lidar Point Cloud Semantic Segmentationmentioning
confidence: 99%
“…In comparison, 2D BEV or RV grid based methods are efficient but only use a single view (either BEV or RV) for processing Li-DAR data. Recent work has investigated the use of multiple views [20,21,22,23,24] and shown that the complementary benefits of both views improve performance. However, these methods use only one frame of LiDAR data and only solve perception tasks such as object detection and semantic segmentation.…”
Section: Lidar Representationmentioning
confidence: 99%